2019
DOI: 10.1111/jgs.16178
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric Elements and Oral Anticoagulant Prescribing in Older Atrial Fibrillation Patients: SAGE‐AF

Abstract: OBJECTIVES Oral anticoagulants are the cornerstone of stroke prevention in high‐risk patients with atrial fibrillation (AF). Geriatric elements, such as cognitive impairment and frailty, commonly occur in these patients and are often cited as reasons for not prescribing oral anticoagulants. We sought to systematically assess geriatric impairments in patients with AF and determine whether they were associated with oral anticoagulant prescribing. DESIGN Cross‐sectional analysis of baseline data from the ongoing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 53 publications
(79 citation statements)
references
References 38 publications
3
70
1
Order By: Relevance
“…We used baseline data from the prospective multi-center study entitled "Systematic Assessment of Geriatric Elements in AF (SAGE-AF)". Details of participant recruitment and study protocols have been described previously [18][19][20]. Participants were recruited from three medical centers in Massachusetts and two medical centers in Central Georgia between 2015 and 2018.…”
Section: Study Populationmentioning
confidence: 99%
“…We used baseline data from the prospective multi-center study entitled "Systematic Assessment of Geriatric Elements in AF (SAGE-AF)". Details of participant recruitment and study protocols have been described previously [18][19][20]. Participants were recruited from three medical centers in Massachusetts and two medical centers in Central Georgia between 2015 and 2018.…”
Section: Study Populationmentioning
confidence: 99%
“…12 Some geriatric-dependent diseases are described as being the reasons for not prescribing oral anticoagulants, which suggests that prescribers may either be unaware of or deliberately ignoring the presence of these factors in clinical settings. 13 Meanwhile, the study of Nguyen et al suggested that the frailty status had little impact on antithrombotic prescriptions and also had no impact on anti-arrhythmic prescriptions. 14 One of the biggest problems in modern geriatrics is frailty syndrome, which is often mistakenly identified with multiple diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The SAGE-AF study has been previously described. ( Saczynski, Sanghai, & Kiefe, 2020 ) In brief, from June 2015 to June 2018, 1244 participants enrolled in SAGE-AF. Enrollment for SAGE-AF is complete and 2 year follow ups are ongoing.…”
Section: Methodsmentioning
confidence: 99%